Maternal and perinatal morbidity and mortality in severe pre-eclampsia and eclampsia in a tertiary care hospital: a prospective study - Chaudhary, Neeta; Tyagi, Natasha; Tyagi, Smita; Singhal, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders of pregnancy are a leading cause of maternal and perinatal morbidity and mortality worldwide. In India, they account for the third most important cause of maternal mortality. The objective of this study was to evaluate maternal and perinatal outcome and complications in cases with severe pre-eclampsia and eclampsia and measures to prevent them. Methods: A prospective study was carried out on 100 patients with severe pre-eclampsia and eclampsia in tertiary care referral hospital over a period of one year i.e. from November 2017 to October 2018. Only those cases with initial blood pressure reading of ≥160/110mmHg or presenting with eclampsia were in included in the study. Detailed history and examination was carried out. Investigations and management were carried out as per standardized department protocol and maternal and fetal outcomes were analyzed. Results: 48% of women were between 21-25 years age, 82% were from rural area, and 86% cases were unbooked, 68% cases were primigravida. Liver Function Tests were deranged in 18% of the patients and 19% had abnormal Renal Function Tests. Labetalol was the most commonly used antihypertensive. Lower segment cesarean section was the mode of delivery in 59% of the cases. Most common maternal complication was Eclampsia. There were 5 maternal deaths i.e. maternal death rate was 5%. 54.3% of live births needed NICU admission and out of these 50% were preterm deliveries. Conclusions: Accessible healthcare and health education and awareness regarding antenatal checkup for all women will lead to early detection of severe pre-eclampsia. Hence, early treatment and management of patient’s complications will certainly improve the maternal and perinatal outcome.